On the new Compound Words in the Polish Press in Lithuania - Davlevič, Miroslav (Slavistica Vilnensis, 2016)
The aim of the article is to present and analyse group compound words that were recently observed in the Polish press in Lithuania. The process of internationalisation of the analysed lexis is connected to the rise of new means of word formation and constituents in the Polish language. As a result, hybrid constructions emerged, i.e., constructions in which foreign international elements of word formation such as: agro-, bio-, cyber-, eko-, euro-, e-, foto-, tele-, wideo- etc are found. The status of the elements of prefix and parts of these compounds is often difficult to determine — we cannot always explain with most certainty — whether the foreign word structure arose on the Polish ground, or was adapted to it and the separation of the morphological element happened only later. The emerging derived words indicate that foreign lexemes are also rooted in the Polish language in Lithuania. Lexems, presented in the article, are a good example of the international words being an evidence of the unified tendencies within the European lexical division.